2013
DOI: 10.1097/dcr.0b013e3182a857eb
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications in Patients With Rectal Cancer Are Associated With Delays in Chemotherapy That Lead to Worse Disease-free and Overall Survival

Abstract: Objective The objective of this study was to identify risk factors for delays in chemotherapy after rectal cancer surgery and evaluate the effects of delayed therapy on long term outcomes. We also sought to clarify what time frame should be used to define delayed adjuvant chemotherapy. Background Postoperative complications have been found to influence timing of chemotherapy in colon cancer patients. Delays in chemotherapy have been shown to be associated with worse overall and disease free survival in color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 19 publications
2
102
0
Order By: Relevance
“…Most studies recommend AC to begin within 8 weeks of curative surgery, although this time frame has been based on data from studies that include primarily colon cancers, despite the different treatment schedules. 8,10,[13][14][15][16][17][18] In this population-based analysis of exclusively stage 2 to 3 rectal cancer patients, an optimal time of 5.6 weeks from date of surgery was found to be significantly associated with improved OS when adjusted for age, gender, performance status, resection margin status, yp stage, and histologic grade.…”
Section: Discussionmentioning
confidence: 92%
“…Most studies recommend AC to begin within 8 weeks of curative surgery, although this time frame has been based on data from studies that include primarily colon cancers, despite the different treatment schedules. 8,10,[13][14][15][16][17][18] In this population-based analysis of exclusively stage 2 to 3 rectal cancer patients, an optimal time of 5.6 weeks from date of surgery was found to be significantly associated with improved OS when adjusted for age, gender, performance status, resection margin status, yp stage, and histologic grade.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with our data, as approximately one third of patients received adjuvant CT greater than 8 weeks after [10] found that the length of postoperative hospital stay, age, and race were associated with initiating CT more than three months following surgery. Postoperative complications have also been associated with delayed initiation of adjuvant CT in rectal cancer patients [17]. In addition to these patient centered factors, systematic factors also contribute to delays in adjuvant CT.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no positive evidence for this delay. In stage III disease, the time to start adjuvant therapy is an important prognostic factor for both colon and rectal cancers 8, 9, 10, 11. Early adjuvant therapy initiation is most often defined as starting therapy within 8 weeks after surgery, and it reportedly reduces the risks of recurrence and increases overall survival (OS) and disease‐free survival 8, 9.…”
Section: Introductionmentioning
confidence: 99%